The creative artistic portfolio and reporting by art education students on their student teaching - Zupančič, Tomaž (Revija za elementarno izobraževanje, 2020)
The study of art education is characterised by the duality of artistic and pedagogical content. The importance of a high-quality intertwining of both segments is emphasised. Various types of portfolios are mentioned. The study focused on how the artistic portfolio and the reports from art teacher trainee students about their student teaching experience can be connected. An innovative model of instruction for the preparation of thestudent teaching report was prepared. Using qualitative analysis procedures, it was established that the creative-pedagogic (CP) model had positive effects on student motivation and generated in-depth introspection. The students worked with the principles of contemporary art, such as juxtaposition, symbolism, performance art, body art, and self-portrait (selfie).
Keywords: art education; student teaching report; art teacher training; contemporary art; higher education